Technical Analysis Plan for Evaluation of the OEO Elementary Education Voucher Demonstration Technical Dissertation. - Rand Corp., Santa Monica, CA.; Rand Corp., Santa Monica, CA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1972)
The purpose of this evaluation is to describe and assess the political, social, economic, and educational outcomes of the voucher demonstration, and the implications of these outcomes for public policy issues. The basic hypotheses of the Demonstration, the basic public policy issues, the major evaluation questions to be considered are set forth, and an organizational framework is specified for the analysis. The salient problems of data analysis and strategies for performing the central tasks of the evaluation are considered. Utilizing 12 specified information categories, the report presents a strategy for the inspection and aggregation of evaluation findings appropriate to address broad issues of public policy and enumerates specific procedures for deriving public policy implications from the evaluation of demonstration outcomes and processes. The plan concludes with discussions of a scheme for the management and organization of the evaluation, a schedule of the work to be performed, and the products to be delivered to OEO. (Author/DN)
Sponsoring Agency: Office of Economic Opportunity, Washington, DC.
Educational level discussed: Elementary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Data Analysis; Data Collection; Educational Change; Educational Finance; Educational Vouchers; Elementary Education; Experimental Programs; Federal Programs; Policy; Program Administration; Program Design; Program Development; Program Evaluation; Program Proposals; Public Policy; Theories; Elementary Education Voucher Demonstration